Vertical profile of night-time stratospheric OClO - Renard, Jean-Baptiste; Lefèvre, Franck; Pirre, Michel; Robert, Claude; Huguenin, D. (HAL CCSD, 1997)
International audience The first night-time observation of the vertical profile of OClO was performed by the AMON balloon-borne spectrometer during the SESAME arctic campaign, launched from Kiruna in northern Scandinavia. The flight, which took place inside the polar vortex on 10 February 1995, reveals mixing ratios of 45+/-10 pptv at 20 km. These results are in excellent agreement with the REPROBUS 3D model simulations, which indicate that the observed OClO corresponds to daytime ClO and BrO mixing ratios of 1.2 ppbv and 10 pptv, respectively.